Estudio de las importaciones con las medidas de salvaguardias que se aplican en el Ecuador periodo 2010 – 2015. - Verdezoto Aguirre, Johana Lizeth (2017)
In the wake of the global crisis that the developing countries went through in 2009, Ecuador has been in need of urgent decisions to resolve the impact of the national economy due to the deficits in the trade balance, The decline of oil and other economic activities; And based directly on the safeguards measures provided for in Article XIX of the GATT 1994, which establishes rules to be applied to the imported product, Rafael Correa, by resolution 011-2015 of the Comex resolves to apply a temporary surcharge to the Imports, in order to safeguard the balance of payments balance, a measure that involves the most important sectors in the country's economy. The main objective of this paper is to analyze the economic impact of safeguards on Ecuadorian imports during the period 2010-2015, as well as to analyze the specific objectives such as: whether the application of safeguards allowed the reduction of imports and improved the Trade balance, or know the sectors that benefit from the application of safeguards, and finally determine which aspects influence the application of safeguards to the importaciones in Ecuador. As a start of work make a brief introduction according to the topic under study, describes the general purpose of study, focusing on information both nationally and internationally, a brief definition was made on international trade and its importance within the World Trade Organization (WTO), imports, safeguards and balance of payments. Among the facts of interest we highlight information on the GATT (General Customs Tariffs and Trade Agreements), in particular on the World Trade Organization (WTO), the documents on safeguard measures and work carried out as a Committee on Safeguards, and a brief analysis On the Andean community (CAN). Its conceptual theoretical basis consists of a description of the epistemological approach of reference, which describes the imports and the application of the measure of Safeguards on them, in addition to the argumeto of Ecuador to apply them. According to analysis carried out, it is determined that in order to balance the trade balance, we must generate foreign exchange through exports, and decrease the amount of imports in our country. In the elaboration of the methodological process, the methods and techniques that were applied in the case of study are detailed, among them information provided by the Central Bank of Ecuador on statistics of imports and the balance of payments during the last years. Imports from neighboring countries were analyzed on the safeguards measure implemented by Ecuador. From the results obtained on the economic Impact of safeguards on imports in Ecuador from 2010 to 2015, positive and negative effects were determined by the application of this measure in our country, after analyzing the work of titration, I have made conclusions and recommendations for The application of these measures that were adopted in order to improve the economy and protect national production.